A review of the literature on intra-lesional immunotherapeutic intervention for the treatment of recalcitrant warts - Mohammed, Ghada; Al-Dhubaibi, Mohammed Saleh; Bahaj, Saleh Salem; AbdElneam , Ahmed Ibrahim (Journal of Pakistan Association of Dermatologists, 2023)
Abstract: Immunotherapeutic intervention has become a crucial treatment modality for the intervention of warts. Immunotherapeutic intervention for warts is typically limited to stubborn lesions. Conventional therapy is not working even though there are numerous immunotherapeutic agents available. Only a few treatment modalities seem to be particularly efficient. Furthermore, evidence-based research is scarce. Data on their efficiency 5-Fluorouracil is typically performed with systemic immunotherapeutic regimens, activated vitamin D, Bleomycin, Interferon (Î±andÎ³), Corynebacterium parvum, trichophyton antigen, measles, mumps, and rubella vaccine, Candida albicans antigen, Mycobacteria; all of these therapeutic approaches have been disclosed to be beneficial for numerous forms of warts. The major part of the mentioned therapies' safety and efficacy have not been assessed in double-blind, controlled clinical studies, attempting to make the reliability and validity of a number of the enumerated therapeutic interventions challenging to assess. This report discusses various types of intra lesional Immunotherapeutic intervention for warts.